DESIGN AND ANALYSIS OF COCONUT EMBRYO CULTURE EXPERIMENTS - Anitha Karun; K. Muralidharan; K. K. Sajini; V.A. Parthasarathy (International Coconut Community Journal, 2003)
The experimental design and data analysis procedures followed for standardizing the CPCRI protocol of coconut zygotic embryo culture are described. The availability of human resources (for initiating the cultures as well as periodic sub-culturing), laboratory space for maintaining culture, infrastructure for preparation of adequate culture media etc, are the important factors to be considered at the planning stage. Since the response of interest per experimental unit is discrete (germinated or not), it is desired to have a “plot size” of 20. Based on the experimental errors obtained for various treatments, attempts were made to obtain the replication size for a specified value of treatment difference to be tested. In most of the experiments, per cent germination was not following the assumption of ANOVA , even after transformation. In such situation, the chi-square test was employed to study the influence of treatments on germination. The coefficient of variation in most of the experiments was below 20 %.